Desempenho agronômico e qualidade de alho nobre livre de vírus em função do tamanho do bulbilho e espaçamento de plantio em região de altitude do semiárido - Lima, Mayky Francley Pereira de (Universidade Federal Rural do Semi-Árido, 2019)
In Brazil, the garlic is a vegetable of great economic and social importance, due to the planted area and the great need of labor. However, although Brazilian productivity has increased in recent years, there is still dependence on imported garlic to meet domestic demand. Thus, in order to change this scenario, management practices such as the manipulation of the spatial arrangement of plants, through changes in spacing between plants, as well as the use of garlic free of virus and associated with clove size, becomes a promising alternative to ensure higher levels of productivity and quality of garlic. Therefore, the objective of this work is to evaluate the production, quality and profitability characteristics of conventional and virus-free garlic as a function of clove size and plant spacing. Two experiments were conducted simultaneously using virus-free and conventional garlic in Portalegre-RN. The experimental design was a randomized block design with four replications. The treatments were arranged in split-plots, the plots being represented by the clove size: large and small. The subplots were composed of four spacings between plants: 7.5, 10.0, 12.5 and 15.0 cm. The data of the experiments were submitted to analyzes of joint variance. Have been evaluated: emergence, number of leaves, height of plants, final stand, cultural cycle, percentage of secondary bulb growth, average bulb mass, total and commercial productivity, bulb classification, number of cloves per bulb, cloves classification, operational cost, gross revenue and net revenue, diameter of bulb, soluble solids, total soluble sugars, titratable acidity, SS/AT ratio, pungency, total solids and industrial index. The use of bulb-free garlic and large clove provided greater vegetative growth, productivity and economic return. The combination of virus-free garlic, large clove and 12.5 cm spacing between plants resulted in higher commercial productivity (11.1 t ha-1) and net revenue (R$ 85,151.00 ha-1). For conventional garlic, the use of large cloves with spacing of 7.5 cm between plants (R $ 25,815.00 ha-1) is suggested. For the quality attributes, vírus-free garlic, as well as the spacings between 12.5 and 15.0 cm promoted greater bulb diameter, titratable acidity, pungency and industrial index, allowing the production of bulbs with better quality and with good prospects for industrialization
Keywords: Allium sativum L; Rentabilidade; Densidade de plantio; Índice industrial; Pungência; Allium sativum L; Profitability; Density of planting; Industrial index; Pungency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA